(untitled) (Mustansiria Dental Journal, 2018)
This study aimed to provide a description of the mesiodistal axial angulation of the maxillary and mandibular teeth in cases of class I malocclusion. The values of the mesiodistal axial angulation of the teeth were measured for 20 subjects (10 males and 10 females) from orthopantomograph using computer program and comparisons were made between the right and left sides and between males and females. The mean values of the mesiodistal axial angulation of the teeth were higher in males than in females, and higher on the right side in upper and lower arches than on the left side for males, females and total sample, however; there was no statistically significant difference between the groups. This study provided a good description of the mesiodistal axial angulation of the maxillary and mandibular teeth in cases of class I malocclusion.